Governance in Pharmaceutical Industry in Developing Countries - Mondlane, Ercília (Revista da UI_IPSantarém, 2023)
The pharmaceutical industry is responsible for processes that involve medicines and health products, which are inputs deemed essential for the human survival. Despite this, it is noted that developing countries face challenges pertaining to the expansion of this industry. “Governance” presents itself as a tool that can lead to improved access and the expansion of companies in this sector. This work, entitled “Governance in the Pharmaceutical Industry in Developing Countries”, aims to analyse the role of governance in the emerging markets in this industry. A systematic revision was carried out and the information was collected through the following database: Scielo, Google Scholar, Scopus and Pubmed. An interview was conducted to Medis Farmacêutica Mozambique. Some of the specific features of development countries are: per capita level of income, poverty, corruption, lack of specialised staff, lack of institutions that assure the attraction and retention of investments. All this result in different speed of development of companies and countries.